Pengembangan Forensic Hypnosis Assesment Instrument For PTSD Mahasiswa Kebidanan Pasca PBL Bersalin - Rita Wahyuni; Aprian Subhananto (Poltekkes Kemenkes Malang, 2020)
Midwives are very susceptible to experiencing PTSD, but STIKES students never admit to experiencing PTSD after completing the Maternity Field Learning Practice because this is a very sensitive matter so that experience and procedures are needed in the approach. If this is allowed, the PTSD will cause the stress to continue to the level of insanity and suicide. For this reason, a Forensic Hypnosis Assessment Instrument For PTSD is needed to detect PTSD experienced by students after the Maternity Field Learning Practice. This research used R dan D research method involving 2 Expert Validator, 1 Practitioner Validator, and 5 postgraduate students who were willing to be sampled on the instrument limited test. Collecting data using interview sheets. The results of the study were a description of the development of the Forensic Hypnosis Assessment Instrument For PTSD for Midwifery Students Post Maternity Field Learning Practice. Forensic Hypnosis Assessment Instrument For PTSD has good criteria from experts and practitioners. It has a huge potential effect on the detection of PTSD after the Field Learning Practice in Maternity. Forensic Hypnosis Assesment Instrument For PTSD is one of product that could give description, knowledge, and new approach for diagnosing candidate of midwives that ever and being PTSD.